Manejo comunicacional en clubes de fútbol femenino - Vidal González, Sammy Kristel (2022)
Women's soccer in Ecuador lives in a constant struggle, despite the fact that it became an official tournament as the Women's Super League, it has not yet managed to capture the interest of the traditional media and much less attention from soccer fans who during They have been used to seeing men running after a ball for decades, giving rise to gender inequality. Currently, social networks have become the fastest and most effective means of communication; women's clubs have turned to these networks, especially Instagram, as their main, or rather, their only means of disseminating their information such as training sessions, days, match dates and those who make up the club as athletes, among others , thus changing a relationship with the public; but this will be effective with excellent communication management, which determines the weak points to strengthen them and the strong ones to promote them. In this way, women's clubs will finally be able to be on everyone's lips like men's soccer, it should be noted that everything will be possible with the support of private and public organizations that promote the dissemination of women's teams.........